The Effectiveness of Yoga Therapy in Reducing Anxiety, Stress and Depression in Women with Multiple Sclerosis - Khadije Janalipour (Caspian Journal of Neurological Sciences, 2017)
Background: Multiple sclerosis (MS) is a progressive chronic neurologic disorder which topically causes the destruction and inflammation of the myelin sheath in the brain and the spinal cord. It also affects the patient's emotions and can be treated using complementary medicine. Objectives: The present study was conducted to investigate the effectiveness of yoga therapy in reducing anxiety, stress and depression in MS patients. Materials and Methods: The present experimental case-control study was conducted using a pretest-posttest approach. The statistical population comprised female MS patients in Rasht, Iran in 2016, 30 of whom were randomly assigned to the control and experimental groups. The experimental group underwent yoga therapy for three months. The two groups completed the depression anxiety stress scale (DASS-21). All the data obtained were analyzed in SPSS-21. p<0.05 was set as the level of statistical significance. Results: The repeated measures ANOVA showed that yoga therapy significantly reduces anxiety, stress and depression in MS patients (p<0.05 for all). Conclusion: The results of the present study revealed that yoga therapy can be widely used as an effective and efficient method to improve the symptoms of anxiety, stress and depression in MS patients. This method can prevent the increasing debilitation in MS patients and help them improve their mood and overcome their anxiety.